2020
DOI: 10.1029/2020ja027837
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the Earth's Polar Outflow From Mid‐Archean to Present

Abstract: The development of habitable conditions on Earth is tightly connected to the evolution of its atmosphere, which is strongly influenced by atmospheric escape. We investigate the evolution of the polar ion outflow from the open field line bundle, which is the dominant escape mechanism for the modern Earth. We perform Direct Simulation Monte Carlo (DSMC) simulations and estimate the upper limits on escape rates from the Earth's open field line bundle starting from 3 gigayears ago (Ga) to present assuming the pres… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 79 publications
(157 reference statements)
0
7
0
Order By: Relevance
“…By using the atmospheric profiles of Tian et al [21], Lichtenegger et al [27] have shown that for 20 XUVʘ an atmosphere with the present-day composition would have been completely eroded within just a few million years by ion-pickup through the then much stronger ancient solar wind [13]. In addition, Kislyakova et al [28] found very strong polar escape rates of N + (5.1 × 10 27 s -1 ) and O+ (4.3 × 10 27 s -1 ) even for much lower fluxes of only about 5 XUVʘ. Such high polar loss rates of ions are also supported by another study [29], which found that exoplanets around K and M stars can lose their entire nitrogen atmosphere within a few 10s to 100s of Myr through ion escape that is induced by the strong solar wind and XUV irradiation in the habitable zones of such stars.…”
Section: Stabilitymentioning
confidence: 99%
“…By using the atmospheric profiles of Tian et al [21], Lichtenegger et al [27] have shown that for 20 XUVʘ an atmosphere with the present-day composition would have been completely eroded within just a few million years by ion-pickup through the then much stronger ancient solar wind [13]. In addition, Kislyakova et al [28] found very strong polar escape rates of N + (5.1 × 10 27 s -1 ) and O+ (4.3 × 10 27 s -1 ) even for much lower fluxes of only about 5 XUVʘ. Such high polar loss rates of ions are also supported by another study [29], which found that exoplanets around K and M stars can lose their entire nitrogen atmosphere within a few 10s to 100s of Myr through ion escape that is induced by the strong solar wind and XUV irradiation in the habitable zones of such stars.…”
Section: Stabilitymentioning
confidence: 99%
“…For higher solar XUV fluxes as expected during the Hadean > 4 Ga, other processes such as solar wind stripping and cold ion outflows of the bulk atmosphere could be important, which might be an additional challenge for sustaining a stable CO 2 -dominated atmosphere. That ion outflow might have been significant during the Hadean eon is already indicated by recent findings of Kislyakova et al (2020) who studied the evolution of early Earth's polar outflow from the mid-Archean to present and already found loss rates due to polar outflow at ≈3 Ga of ≈ 3.3 × 10 27 s −1 and ≈ 2.5 × 10 27 s −1 for O + and N + ions. According to their results, the main parameters that governed the atmospheric escape during the studied time period are the evolution of the young Sun's XUV radiation and the atmosphere composition, while the evolution of the Earth's magnetic field had a less important role.…”
mentioning
confidence: 70%
“…Given our present knowledge, it is difficult to estimate how these severely altered conditions (which also apply to young solar-like stars) will affect atmospheric escape, particularly at magnetized planets. Kislyakova et al (2020) investigated polar escape at Earth for different EUV fluxes ranging back until the Archean eon. They found a significant increase in the polar loss of nitrogen and oxygen within their model from presently 2.1 × 10 26 s −1 and 8.4 × 10 24 s −1 for O + and N + to 1.6 × 10 27 s −1 and 5.6 × 10 26 s −1 at 2.5 Ga (or 7.6 and 66.7 times more respectively).…”
Section: Atmospheric Escape and Importance Of A Magnetic Fieldmentioning
confidence: 99%